Nanostructured crystalline comb polymer of perylenebisimide by directed self-assembly: poly(4-vinylpyridine)-pentadecylphenol perylenebisimide - Narayan, Rekha; Kumar, Prashant; Narayan, K. S.; Asha, S. K. (Advanced Functional Materials, 2013)
Well defined nanostructured polymeric supramolecular assemblies are formed when an asymmetric perylenebisimide substituted with ethylhexyl chains on one end and functionalized with 3-pentadecylphenol at the other termini (PDP-UPBI) is complexed with poly(4-vinylpyridine) (P4VP) via a non-covalent specific interaction such as hydrogen-bonding. The resulting P4VP(PDP-UPBI)(n) complexes are fully solution processable. The bulk structure and morphologies of the supramolecular film studied using small angle and wide angle X-ray scattering reveals highly crystalline nature of the complex. Thin film morphology of the 1:1 complex analyzed using transmission electron microscopy shows uniform lamellar structures in the domain range of 5-10 nm. A clear trend of improved electrical parameters in P4VP(PDP-UPBI) system compared to pristine (PDP-UPBI) is observed from space charge limited current measurements. In short, a simple and facile method to obtain spatially defined organization of n-type semiconductor perylenebisimide molecules using hydrogen bonding interactions with P4VP as the structural motif is showcased herein.